Identifying differences in the experience of (in)authenticity: a latent class analysis approach - Lenton, Alison P.; Slabu, Letitia; Bruder, Martin; Sedikides, Constantine (Frontiers in Psychology, 2014)
Generally, psychologists consider state authenticity– that is, the subjective sense of being one’s true self – to be a unitary and unidimensional construct, such that (a) the phenomenological experience of authenticity is thought to be similar no matter its trigger, and (b) inauthenticity is thought to be simply the opposing pole (on the same underlying construct) of authenticity. Using latent class analysis, we put this conceptualization to a test. In order to avoid over-reliance on a Western conceptualization of authenticity, we used a cross-cultural sample (N = 543), comprising participants from Western, South-Asian, East-Asian, and South-East Asian cultures. Participants provided either a narrative in which the described when they felt most like being themselves or one in which they described when they felt least like being themselves. The analysis identified six distinct classes of experiences: two authenticity classes ('everyday' and 'extraordinary'), three inauthenticity classes ('self-conscious,' 'deflated,' and 'extraordinary'), and a class representing convergence between authenticity and inauthenticity. The classes were phenomenologically distinct, especially with respect to negative affect, private and public self-consciousness, and self-esteem. Furthermore, relatively more interdependent cultures were less likely to report experiences of extraordinary (in)authenticity than relatively more independent cultures. Understanding the many facets of (in)authenticity may enable researchers to connect different findings and explain why the attainment of authenticity can be difficult.